2018
DOI: 10.1177/0023830917753237
|View full text |Cite
|
Sign up to set email alerts
|

Do Persian Native Speakers Prosodically Mark Wh-in-situ Questions?

Abstract: It has been shown that prosody contributes to the contrast between declarativity and interrogativity, notably in interrogative utterances lacking lexico-syntactic features of interrogativity. Accordingly, it may be proposed that prosody plays a role in marking wh-in-situ questions in which the interrogativity feature (the wh-phrase) does not move to sentence-initial position, as, for example, in Persian. This paper examines whether prosody distinguishes Persian wh-in-situ questions from declaratives in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 48 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…3 The main pitch accent in BP falls on the last word of the sentence by default (Gebara, 1976). 4 As a preliminary step, we need to know whether the prosodic characteristics we found in the production experiment (Shiamizadeh et al 2016) are perceptible by Persian native speakers. Therefore, we conducted this simple perception study before running a gating experiment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 The main pitch accent in BP falls on the last word of the sentence by default (Gebara, 1976). 4 As a preliminary step, we need to know whether the prosodic characteristics we found in the production experiment (Shiamizadeh et al 2016) are perceptible by Persian native speakers. Therefore, we conducted this simple perception study before running a gating experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Shiamizadeh et al (2016) compared prosodic correlates of wh-in-situ questions and their declarative counterparts. They found that a higher level of pitch register, a higher F0 onset and a shorter duration distinguished the pre-wh part in wh-questions from declaratives.…”
Section: Prosodic Correlates Of Persian Wh-in-situ Questionsmentioning
confidence: 99%
See 3 more Smart Citations